2023
DOI: 10.1186/s12964-023-01079-3
|View full text |Cite
|
Sign up to set email alerts
|

The role and mechanism of action of tRNA-derived fragments in the diagnosis and treatment of malignant tumors

Abstract: Cancer is a leading cause of morbidity and death worldwide. While various factors are established as causing malignant tumors, the mechanisms underlying cancer development remain poorly understood. Early diagnosis and the development of effective treatments for cancer are important research topics. Transfer RNA (tRNA), the most abundant class of RNA molecules in the human transcriptome, participates in both protein synthesis and cellular metabolic processes. tRNA-derived fragments (tRFs) are produced by specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 136 publications
0
2
0
Order By: Relevance
“…The non-canonical Wnt signaling is critical for the osteogenic differentiation 43 , 44 , a study pointed out that activation of the non-canonical Wnt signaling pathway in human mesenchymal stromal cells increases osteogenic differentiation and counteract the osteoclastic effects of MM cells, and further suggest that non-canonical Wnt signaling may be a therapeutic target for MM-related bone disease 45 . An increasing number of studies have shown that tRNA abundance increases significantly in cancer, suggesting that it may be a factor in cancer progression 46 . A study reported that abnormally high translation activity exists in MM cells and is mediated by high abundance of tRNA, and that application of proteasome inhibitors reduced aminoacyl tRNA biosynthesis 47 .…”
Section: Discussionmentioning
confidence: 99%
“…The non-canonical Wnt signaling is critical for the osteogenic differentiation 43 , 44 , a study pointed out that activation of the non-canonical Wnt signaling pathway in human mesenchymal stromal cells increases osteogenic differentiation and counteract the osteoclastic effects of MM cells, and further suggest that non-canonical Wnt signaling may be a therapeutic target for MM-related bone disease 45 . An increasing number of studies have shown that tRNA abundance increases significantly in cancer, suggesting that it may be a factor in cancer progression 46 . A study reported that abnormally high translation activity exists in MM cells and is mediated by high abundance of tRNA, and that application of proteasome inhibitors reduced aminoacyl tRNA biosynthesis 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, both miRNA and tRF expression can fluctuate depending on stage of life, immune regulations, disease, and other biological processes within an organism [16,17,[58][59][60][61]. Since samples were collected at a single time point (14 days of age), temporal studies should be completed to assess the differential expression of small non-coding RNAs in calves to achieve a clear understanding of the epigenetic effects a BLV-infected dam plays on a calf's post-natal development.…”
Section: Discussionmentioning
confidence: 99%